Early postoperative complications and local relapses after nipple sparing mastectomy and immediate breast reconstruction using silicone implants - Selaković, Vladimir; Ranisavljević, Milan; Radovanović, Zoran; Vicko, Ferenc; Lukić, Dejan; Đurić, Mladen (Archive of Oncology, 2019)
Purpose of this study was to evaluate early complications and risk factors associated with nipple sparing mastectomy and immediate breast reconstruction. Methods: This retrospective study was made using data from 246 breast cancer patients treated at the Oncology Institute of Vojvodina in the period from January 2010 to December 2015. In all patients nipple sparing mastectomy was performed along with primary breast reconstruction. Results: The mean indication for nipple sparing mastectomy was multicentricity of the tumor (114 patients; 46.3%). The majority of surgically treated patients were in stage II of the disease. The total percentage of local relapses after the nipple sparing mastectomy was 1.6% (4 patients). Total percentage of early complications was 15% (37 patients). Median follow-up after nipple sparing mastectomy was 260 weeks (ranging from 417 to 104 weeks). Conclusion: Primary reconstruction of the breasts using heterologous implants is standard surgical procedure for breast cancer that does not lead to increased number of complications, nor to increased percentage of the local recurrence.
Keywords: Nipples; Local relapses; Breast cancer; Postoperative Complications; Mastectomy